Konjungtivitis pada COVID-19 - Airina Stefanie; Stefanny Haryady; Yufilia Suci Amelia (Cermin Dunia Kedokteran, 2021)
Corona Virus Disease 19 (COVID-19) pertama ditemukan di Wuhan, Cina, pada Desember 2019 dan telah menjadi ancaman kesehatan global. COVID-19 disebabkan oleh Severe Acute Respiratory Corona Virus 2 (SARS-CoV-2), ditransmisikan melalui droplet pernapasan atau kontak erat. Penelitian terbaru menyatakan bahwa konjungtiva dapat menjadi port d’entree SARS-CoV-2, dan menyebabkan gejala konjungtivitis. Jalur transmisi SARS-CoV 2 ke okuler diduga melalui inokulasi langsung dan melalui reseptor ACE2 yang diekspresikan di konjungtiva. Karakteristik konjungtivitis COVID-19 adalah sekret mukoid ataupun aqueous berlebih, sensasi tidak nyaman pada okuler seperti gatal, benda asing, atau rasa terbakar, serta hiperemis konjungtiva. Pada pemeriksaan RT PCR swab okuler ataupun nasofaring dapat positif pada 3 hingga 21 hari setelah onset gejala. Studi ini merupakan literature review. Artikel diambil dari database Google scholar, Pubmed, Lange, Elsevier, dengan kata kunci “ocular manifestation in COVID-19”, “characteristics of conjunctivitis in COVID-19”, “mechanism of COVID-19 in conjunctiva”. Artikel yang dipilih adalah jurnal yang dipublikasi sejak tanggal 1 Desember 2019 sampai 30 Oktober 2020. Corona Virus Disease 19 (COVID-19) was first discovered in Wuhan, China, in 2019 and has been declared as global health emergency. COVID-19 is caused by Severe Acute Respiratory Corona Virus 2 (SARS-CoV 2) transmitted through droplet and physical contact. Studies stated that conjunctiva is a potential port of entry of SARS-CoV2, which then leads to conjunctivitis. This literature review is based on analytic study on conjunctivitis in COVID-19. The transmission route is thought from direct inoculation and expression of ACE2 receptors from conjunctiva. Most common characteristics of conjunctivitis in COVID-19 are increased conjunctival secretions both mucoid and aqueous, and ocular discomfort such as itching, foreign bodies sensations, burning, and conjunctival hyperemia. RT PCR from both ocular and nasopharyngeal swabs were detectable from days 3 to 21 after the onset of symptoms. This study is a review on published articles from December 1st 2019 to October 30th 2020, in Google Scholar, PubMed, Lange, and Elsevier; selected with keywords “ocular manifestation in COVID-19”, “characteristics of conjunctivitis in COVID-19”, “mechanism of COVID-19 in conjunctiva”.